Subordination preserving properties associated with a class of operators - Poonam Sharma (Le Matematiche, 2013)
The purpose of this paper is to find some subordination preserving properties of analytic functions associated with a class of operators with complex parameters. Due to the compositional structure of the involved operator, we take its advantage in deducing results which involve more familiar operators, thereby, exhibiting the usefulness of the main results.